(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This thesis examines the growing role of the English language in shaping the cultural identity of urban Uzbek-speaking youth. As English continues to gain prominence in education, media, and social communication, it has emerged as a powerful agent of cultural transformation. Drawing on sociolinguistic theories and field data, the study investigates how English usage contributes to the construction of hybrid identities that reflect both local traditions and global influences. The findings reveal that English serves not only as a communicative tool but also as a symbol of modernity, opportunity, and cultural affiliation, especially among younger generations in urban centers such as Tashkent and Samarkand.